On Rational Choice, Risk and Utility in Mobile Banking - Njenga, Kennedy; Ndlovu, Sifiso (My University, 2013)
The diffusion of mobile banking technology offers an opportunity for analysis of the risk associated with the protection of information of banking clientele. There is emerging discourse with regard to clientele awareness of privacy issues. This article conceptualises banking clientele awareness of specific issues such as risk, security and information privacy policies. The key concern is the impact such awareness has on subscribers choosing to continue their use of mobile banking services. The article attempts to explain the utility/risk trade-off and how this affects the clients’ willingness to continue subscribing to mobile banking services, using quantitative analysis and rational choice theory (RCT). Purposeful sampling targeted South African bank account-holders. Empirical results show that consumer willingness to continue to use mobile banking services is largely driven by the perceived utility of the service, while privacy risk is not a significant deterrent. This is an important finding in the context of banks encouraging consumers to use mobile banking systems, for the banks to achieve retail growth. This creates a greater responsibility for banks to manage consumer risk. The findings may be more broadly pertinent in the SADC region and on the African continent, where telecoms firms engaged in mobile banking services must also attend to issues of consumer risk; and where R&D investment in the field of information security is highly desirable.
Keywords: mobile banking, privacy, risk, utility, rational choice theory